Psychological Well-Being and Social Functioning Across the Cancer Stages: Implications for Palliative Care. Issue 2 (3rd July 2018) - Ndetei, David; Musyimi, Christine; Tele, Albert; Musau, Abednego; Gitonga, Isaiah; Mutiso, Victoria
Abstract: Studies conducted regarding cancer care have mainly focused on the management of physical conditions, with few studies assessing psychological well-being throughout illness course. This cross-sectional study (n = 389) examined the psychological well-being and social functioning of patients with cancer across cancer stages, among adult patients attending a cancer clinic at a public referral hospital in Kenya. Social and occupational functioning entails the ability to interact optimally with one's environments including work, social activities, and relationships and fulfill the roles within such environments, as well as engage in meaningful activities of daily life. Psychological well-being, on the other hand, is a dynamic concept that includes subjective, social, and psychological dimensions and health-related behaviors. We used various measures to assess different facets of respondent's life and psychological well-being. Results showed that cancer status was negatively associated with social and occupational functioning and psychological well-being. Results also revealed that increasing severity of an individual's cancer disease placed them at a higher risk of disability and psychological impairment. To reduce this risk, routine psychological care across the disease continuum is recommended.